Food selectivity and weight status in children with an Autism Spectrum Disorder (ASD) - Withrow-McDonald, Nicole A., author; Harris, Mary, advisor; Johnson, Susan L., advisor; Anderson, Jennifer, committee member; Davies, Patricia, committee member (Colorado State University. Libraries, 2014)
To view the abstract, please see the full text of the document.
Keywords: autism spectrum disorders; BMI; food selectivity; macronutrient intake; micronutrient intake; weight